READ Methodology: Community Library and Resource Center a Transformative Instrument in Socio-Economic Development - Magar, Pawan Rana (Journal of Multidisciplinary Research Advancements, 2024)
READ methodology focuses on setting up the “Community Library and Resource Centers,” which stimulates social and economic transformation integrating with education, enterprise, and community development, collaborations with rural communities, and to seed for-profit sustaining enterprises to ensure their durable functioning and success. Within the demand from the community, the READ CLRC service delivery mechanism of the room library model was further expanded into a children’s section, women’s section, youth section, information, communication and technology section, meeting hall, and audio / visual section. CLRCs also partner with local government, community people, and other stakeholders to deliver community outreach activities such as practical action programs which basically address the issues related to agriculture and livestock, income-generating skills, health sessions, literacy classes, safe migration, disaster risk reduction, social institutional and cooperative literacy and etc. The systematic review approach was used for analysis because it detects themes, theoretical perspectives, or common issues within a specific research discipline or methodology or identifies a theoretical concept’s components. This paper examines the READ methodology as a transformative instrument for socio-economic development that aligns with Madon’s theoretical model and the DFID Sustainable Livelihood Framework. So, in this order, various literature and focus group discussion findings have demonstrated strong evidence that READ methodology can be recommended as a transformative instrument in community development driven locally.